2021
DOI: 10.1149/1945-7111/abf266
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Tungsten from Molten KF–KCl–WO3 and CsF–CsCl–WO3

Abstract: The electrodeposition of W films was investigated in KF-KCl eutectic melts after adding 0.5-2.0 mol% of WO6 at 923 K. Cyclic voltammetry at a Ag electrode suggested that the electrodeposition of W from W(VI) ions proceeds from 1.65 V vs. K + /K. Electrodeposition of α-W was confirmed by XRD analysis. The effect of current density and added amount of WO3 on the morphology of W films was investigated by surface and crosssectional SEM, which indicated that the best W film having thickness of ca. 15 μm was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…From the cyclic voltammogram in KF–KCl–WO 3 shown in Figure b, the cathodic current due to W deposition is observed at approximately 1.6 V vs K + /K. Galvanostatic electrolysis was then conducted at the Cu electrode Figure c shows the Cu electrode before and after electrodeposition.…”
Section: Electrodeposition Of Tungstenmentioning
confidence: 99%
“…From the cyclic voltammogram in KF–KCl–WO 3 shown in Figure b, the cathodic current due to W deposition is observed at approximately 1.6 V vs K + /K. Galvanostatic electrolysis was then conducted at the Cu electrode Figure c shows the Cu electrode before and after electrodeposition.…”
Section: Electrodeposition Of Tungstenmentioning
confidence: 99%
“…[1][2][3] The Na 2 WO 4 -WO 3 molten salt system is predominantly utilized for tungsten coating since WO 3 is stable and relatively easy to prepare. [4][5][6] Electrodeposition of tungsten with molten salts as a medium is an effective approach in the production of tungsten coatings [7][8][9][10][11][12] and has garnered considerable attention. [13][14][15][16][17][18] In terms of electrode selection, studies have suggested that copper electrodes in Na 2 WO 4 -WO 3 molten salt can produce dense tungsten coatings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, according to research, 16 tungsten trioxide cannot be electrochemically reduced to tungsten metal in the eutectic melt of sodium and calcium chlorides without large losses, while the worksproof that this process can be implemented in molten mixtures of LiCl-KCl and KF-KCl, CsF-CsCl. 17,18 There is no information on large losses of tungsten due to the formation and sublimation of volatile tungsten compounds. Given the above, the study of the processes that occur during the electrochemical reduction of tungsten oxide is an important not only applied but also scientific task.…”
Section: Introductionmentioning
confidence: 99%